Handbook of animal-based fermented food and beverage technology - Hui, Y. H.; Evranuz, E. Özgül; Chandan, Ramesh C. (CRC Press, 2012)
"Completely revised and updated, this second edition includes new sections on fermented seafood such as fish sauce, updated U.S. standards, and permitted food ingredients derived from each fermented product. An international panel of experts from government, industry, and academia provide an in-depth review of fermentation history, microorganisms, quality assurance practices, and manufacturing guidelines"-- Provided by publisher.
Rev. ed. of: Handbook of food and beverage fermentation technology / edited by Y.H. Hui ... [et al.]. 2004.
"Handbook of food and beverage fermentation technology" is the first edition of "Handbook of plant-based fermented food and beverage technology" and "Handbook of animal-based fermented food and beverage technology."
Keywords: Fermented foods -- Handbooks, manuals, etc.; Beverages -- Microbiology -- Handbooks, manuals, etc.; Fermentation -- Handbooks, manuals, etc.; Food of animal origin -- Handbooks, manuals, etc.; Animal products -- Handbooks, manuals, etc.; elektronické knihy; electronic books